If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + -1x + -2y + -5x = 0 Reorder the terms: -1x + -5x + -3y + -2y = 0 Combine like terms: -1x + -5x = -6x -6x + -3y + -2y = 0 Combine like terms: -3y + -2y = -5y -6x + -5y = 0 Solving -6x + -5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. -6x + -5y + 5y = 0 + 5y Combine like terms: -5y + 5y = 0 -6x + 0 = 0 + 5y -6x = 0 + 5y Remove the zero: -6x = 5y Divide each side by '-6'. x = -0.8333333333y Simplifying x = -0.8333333333y
| 3-2x=512 | | -6x+4(5x-6)=-116 | | 8(a)+4(b)=28 | | 3r-4(5r+7)=37-4r | | 1/8=4d | | x^(x*x^(1/2))=(x*x^(1/2))^x | | y=cost(5+9) | | 3ln(4x+5)=14 | | 49-(-3)=-5x+10-x | | (7*35)+(x*0.14)=(7*70)+(x*0.07) | | -9=-2(k+5)+-15 | | 2(s+1)=-2 | | -3r+-1=2r+16+-7 | | W/8=-26 | | -(c+14)=2 | | 4x^2-21x-135=0 | | 99=-6m-(7m+5) | | 3x-14+2(x-4)=2x-2 | | 19=2(b+20)-(-17) | | 1.7=0.22 | | (7*35)+(x*.14)=(7*70)+(x*.07) | | 107-11b=-1b+37 | | y-4/-3=9 | | -32(11x)+27(14x)=0+-296 | | 0=16+4x+x^2 | | =(9x)+(3x-5) | | 12=7-3x | | 3d+2d= | | 2(1+6x)+2(3-6x)=7x-3x | | (9x)+(3x-5)= | | 50+60x=-84+210x | | 35+(x*.14)=70+(x*.07) |